Investigation of chemical, sensory, and rheological properties of Kyrgyz ethnic fermented beverage from cereals during cold storage - Jamila Smanalieva; Janyl Iskakova (MANAS: Journal of Engineering)
Maksym is a Kyrgyz ethnic beverage made from milled cereals such as wheat, barley, or maize, boiled in water, and then fermented using yeast and lactic acid bacteria as a starter culture. The aim of this study was to investigate the changes in the consistency and sensory properties of Maksym after industrial production during refrigerated storage. The acidity of the beverage increases and the total soluble solids decrease after 21 days. The amount of lactic acid bacteria (LAB) and yeast after production were 9.36 and 9.46 log cfu/mL, respectively. After 21 days it is indicated that the amount of both starter cultures decreased by 2 log units. In terms of acceptability, the sensory properties after 7 days of storage received the highest rating. However, the acidic taste after 21 days of storage received the lowest rating. Rheological measurements carried out at 5, 10, 20, and 30°C also revealed these changes. Four rheological models (Newtonian, Herschel-Bulkley, Ostwald De-Waele, and Casson) were used to describe the flow behaviour of the beverage. The Casson model was superior to other rheological models. The effective viscosity of Maksym was decreased from 2.66 to 1.96 mPa·s after 21 days of cold storage. The activation energy was decreased from 23.10 and 14.94 kJ/mol and indicated the thinning of viscosity of the beverage. The obtained parameters can be used to predict the shelf-life model and product labelling by its expiry period, as well as to control the quality of Maksym.